Manajemen Pembelajaran dalam Meningkatkan Prestasi Belajar Siswa - Siti Sofiyah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2022)
The purpose of this research is to provide information on planning, implementing and evaluating learning to improve student performance. This study uses qualitative methods. The survey was conducted from March to June 2022 at MIN 3 Purworejo. Informants for this survey were madrasah leaders, teachers and students. Data collection techniques using interviews, observations and documentation. Validity of data using triangulation. Data analysis uses the Miles & Huberman model, which consists of data collection, data reduction, data display, and inference. The results of this study show that: (1) Teachers implement lesson plans by creating curricula, annual programs, semester programs, KKM, time allocation, learning implementation plans, support and enhancement programs. (2) The delivery of learning is performed by teachers, including preparatory activities (perception), core activities (including exploration, elaboration, and validation), and conclusion activities. Teachers use learning media and apply different learning methods. (3) Evaluation of learning is done by teachers and heads of madrasas. Teachers implement assessment systems in the form of learning processes and learning outcomes. This includes her three areas: cognitive, psychomotor, emotional. Madrasah principals regularly monitor teachers to improve their performance